Analysis of fishermen's economic welfare in Pinrang regency, South Sulawesi: Integrating institutional empowerment, infrastructure development, and productivity for sustainable livelihoods - Hamzah, Suharwan; Maryunani, Maryunani; Multifiah, Multifiah; Satria, Dias (Edelweiss Applied Science and Technology, 2025)
This research analyzes the factors that can influence the economic welfare of fishermen in Pinrang Regency, South Sulawesi, focusing on the integration of institutional empowerment, infrastructure development, and productivity for sustainable livelihoods. It employs a quantitative research approach, collecting primary data from 95 respondents using a questionnaire. The research variables include institutional empowerment, fishermen empowerment, infrastructure, productivity, and welfare, with data analyzed using Structural Equation Modeling (SEM-PLS). The findings indicate that institutional empowerment and infrastructure development significantly affect fishermen's productivity, which in turn positively impacts their welfare. However, fishermen empowerment did not show a significant impact on fishermen's productivity. The study concludes that a holistic approach, integrating these key factors, is essential to improve the economic welfare of fishermen in Pinrang Regency. Recommendations for local governments include strengthening institutions, improving infrastructure, and promoting sustainable fishing practices to achieve long-term improvements in fishermen's welfare.